Clinical success of IPS empress II Inlays/Onlays - (:unkn) unknown (Trans Tech Publications Ltd, 2012)
For the dental restorations, ceramic materials have increasing popularities because of their biocompatibility and superior esthetics. IPS Empress which is leucite-reinforced glass ceramic is one of the most popular ceramics. IPS Empress II was developed in following years which is stronger than IPS Empress. In the dental applications some problems occur about ceramic restorations. Hence,this study was performed to examine the six-year clinical performance of IPS Empress II ceramic onlay and inlay restorations. © (2012) Trans Tech Publications.
Keywords: Clinical performance of IPS empress; Dental restorations; IPS empress